Relationships between Physical Working Environment Employee Well-being, and Employee Commitment in Hospital Management - Nadia, Nadia; Fathurahman, Heri (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
The purpose of this article is to analyze relationships between physical conditions of the working environment and employee well-being as well as to analyze relationships between employee well-being with employee commitment in a profession that deals intensively with high level of job stress. The study uses a quantitative approach and involves 72 respondents of medical employee in Brawijaya Women & Children Hospital at South Jakarta, taking into account its recent operational establishment and a business specialty in women and children healthcare. Data was collected through a survey in 2012 by using questionnaire as a research instrument. We adopt Likert scaling with data analysis technique uses Rank Spearman method. The hypothesis is tested using Z-test. Exploratory factor analysis confirms that the measurement scales used in this study met the acceptable standards of validity and reliability analysis. Furthermore, the Rank Spearman correlation analysis shows two important findings: first, physical condition of working environment is significantly correlated with employee well-being; second, employee well-being is significantly correlated with employee commitment.